Genetic cardiomyopathies - Kloos, Wanda; Katus, Hugo; Meder, Benjamin (Herz, 2012)
Dilated cardiomyopathy (DCM) is a multifactorial disease of the heart muscle and a leading cause of congestive heart failure. Human genetic studies and the establishment of suitable animal models such as mice and zebrafish have already revealed parts of its genetic etiology. With the next generation of genomic sequencing technologies (NGS) on the rise, the comprehensive genetic dissection of DCM patients will reveal clinically relevant information, novel causes, and modifiers of this complex disorder. The recent exploration of the epigenome as another mechanism of cardiac gene regulation will further elucidate unexplained variations observed in the correlation between the patient’s genotype and phenotype. Some of these intriguing advances being made in basic genetic research will soon find their way into clinical practice for more individualized treatment of cardiomyopathy patients.